Enhancing 'First 1,000 Days' Nutrition Literacy via a Posyandu Kader 'Train-the-Trainer' Model: A Mixed-Methods Impact Evaluation on Child Nutritional Status in Eastern Indonesia - Fatimah Mursyid; Novalika Kurnia; Sana Ullah; Lestini Wulansari; Muhammad Yoshandi (HM Publisher, 2025)
The 'First 1,000 Days' (HPK) period is critical for preventing stunting, a significant public health challenge in Indonesia, particularly in Eastern provinces. Posyandu kader (community health volunteers) are pivotal, but their effectiveness is often hampered by inadequate and unstandardized training. This study evaluates the impact of a structured 'Train-the-Trainer' (ToT) model on kader nutrition literacy and, subsequently, on child nutritional status. We conducted a quasi-experimental, convergent parallel mixed-methods study in two districts of East Nusa Tenggara (NTT) province, Indonesia. The intervention district (n=50 kader, n=312 mother-child dyads) received the ToT intervention, while the control district (n=50 kader, n=309 mother-child dyads) continued standard practices. The ToT model involved training Puskesmas (health center) staff as 'Master Trainers' who then cascaded structured training and mentorship to kader over 12 months. Quantitative data (kader literacy scores, child anthropometry [Height-for-Age Z-score, HAZ]) were collected at baseline and 12-month follow-up, analyzed using Difference-in-Differences (DiD) and linear mixed-effects models (LMM). Qualitative data (n=24 in-depth interviews, n=6 focus group discussions) explored the intervention's mechanisms, fidelity, and contextual facilitators. At 12 months, kader nutrition literacy in the intervention group increased significantly (mean score change: +29.8 points) compared to the control group (+2.1 points, p < 0.001). The LMM analysis, controlling for covariates, showed a significant 'time × group' interaction effect on child HAZ (β = 0.28, 95% CI [0.15, 0.41], p < 0.001), indicating a meaningful improvement in child growth attributable to the intervention. Stunting prevalence (HAZ < -2 SD) in the intervention group decreased by 8.7 percentage points, while it remained stagnant in the control group. Qualitative themes revealed that the ToT model enhanced kader self-efficacy, shifted their role from passive data collectors to active counselors, and provided mechanisms to address local socio-cultural barriers to nutrition. In conclusion, the 'Train-the-Trainer' model is an effective and scalable strategy for enhancing kader nutrition literacy and precipitating measurable improvements in child nutritional status in high-burden settings. This model provides a sustainable framework for strengthening community health systems to combat stunting, aligning with Indonesia's national strategy and Sustainable Development Goal 3.